Pengembangan Media Focusky Materi Interaksi Keruangan Desa Dan Kota Di SMA Negeri 1 Suwawa Kabupaten Bone Bolango - Fajran Bentearu; Fitryane Lihawa; Sri Maryati; Daud Yusuf (UNM Geographic Journal, 2023)
The purpose of this study is to develop video-animated learning media using the Focusky application on the material of Village and City Spatial Interaction. The purpose of this study is to develop video-animation-based learning media using focusky applications on village and city spatial interaction materials. Focusky is an application that has a variety of templates that can be used in making learning media, especially on village and city interaction materials. This study used the ADDIE model development research method as an approach in compiling the learning media. Media validation is carried out by material experts, media experts, and learning experts. This learning media was tested on a limited and general scale on a limited scale of 17 students each and a general scale of 41 students taken from two schools namely SMA N 1 Suwawa and SMA Negeri 1 Kabila by using a questionnaire or questionnaire. Data from development research results were obtained from the results of the validator which showed that this learning media was declared feasible to use and included in the very valid category. Validation by material experts gets a percentage value of 90% included in the very valid category, media experts get a percentage value of 75%, and learning experts give very valid values with percentages of 86.66% and 88%. The average student response to learning media is 78.18% for a limited scale and 81,68% for a general scale